Kontribusi Produk Pembiayaan terhadap Kinerja Profitabilitas : Bukti Empiris dari Bank Mega Syariah - Salim Salamah Majdi; Pranoto Effendi; Asgaft Asy Syad Rasyid (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Sharia financing is a key instrument that Islamic banks must promote in channeling third-party funds. This aligns with the basic principles of Islamic banking, which emphasize fairness, partnership, and business sustainability. Therefore, it is crucial to examine how various Islamic financing schemes impact Islamic bank profitability. This study focuses on Bank Mega Syariah, using secondary data sourced from quarterly financial reports for the period 2017 to 2024. The financing variables analyzed include musyarakah, mudharabah, murabahah, and ijarah, while profitability is measured using relevant financial performance indicators. The analysis method used is a quantitative approach using regression techniques to examine the effect of each type of financing on bank profitability. The results show that musyarakah, mudharabah, and murabahah-based financing have a positive and significant impact on profitability, meaning that the higher the distribution of these three types of financing, the greater their contribution to increasing bank profits. These findings indicate that the business partnership model, profit-sharing system, and profit margin stipulated in the murabahah contract significantly contribute to maintaining profit growth. Conversely, ijarah financing did not significantly impact profitability. This may be due to the characteristics of ijarah, which tends to be oriented towards fixed assets or leases, resulting in a relatively limited contribution to increasing short-term profits. Overall, this study provides important implications for Islamic bank management to further optimize the proportion of musyarakah, mudharabah, and murabahah financing as a strategy to boost financial performance and maintain business continuity amidst the competitive Islamic banking industry.